Mucolipidosis type IV and the mucolipins. (24th November 2010) - Bach, Gideon; Zeevi, David A.; Frumkin, Ayala; Kogot-Levin, Aviram
Abstract : MLIV (mucolipidosis type IV) is a neurodegenerative lysosomal storage disorder caused by mutations in MCOLN1, a gene that encodes TRPML1 (mucolipin-1), a member of the TRPML (transient receptor potential mucolipin) cation channels. Two additional homologues are TRPML2 and TRPML3 comprising the TRPML subgroup in the TRP superfamily. The three proteins play apparently key roles along the endocytosis process, and thus their cellular localization varies among the different group members. Thus TRPML1 is localized exclusively to late endosomes and lysosomes, TRPML2 is primarily located in the recycling clathrin-independent GPI (glycosylphosphatidylinositol)-anchored proteins and early endosomes, and TRPML3 is primarily located in early endosomes. Apparently, all three proteins' main physiological function underlies Ca 2+ channelling, regulating the endocytosis process. Recent findings also indicate that the three TRPML proteins form heteromeric complexes at least in some of their cellular content. The physiological role of these complexes in lysosomal function remains to be elucidated, as well as their effect on the pathophysiology of MLIV. Another open question is whether any one of the TRPMLs bears additional function in channel activity